2013
DOI: 10.5005/jp-journals-10013-1173
|View full text |Cite
|
Sign up to set email alerts
|

Large Frontal Sinus Mucopyocele

Abstract: A mucocele is an epithelial-lined, mucus-containing sac completely filling the sinus and capable of expansion. This is in contradistinction to a blocked sinus cavity which simply contains mucus within the sinus. The frontal sinus is most commonly involved, whereas sphenoid, ethmoid, and maxillary mucoceles are rare. Frontal sinus is present just above the orbital cavity so any mass causing the expansion of floor of the frontal sinus leads to outwards (proptosis), downward and lateral displacement of orbit. If … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Some lesions may demonstrate regular linear peripheral enhancement after the administration of a contrast medium [ 8 ]. Shukla et al concluded that mucocele contents often become increasingly desiccated and have higher protein content over time, leading to hyperdensity on CT scans and variable degrees of hyperintensity on T1-weighted and hypointensity on T2-weighted MRI sequences [ 2 ]. In our case, the mucocele displayed isodensity on the CT scan, low signal intensity on T1-weighted images, and high signal intensity on T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some lesions may demonstrate regular linear peripheral enhancement after the administration of a contrast medium [ 8 ]. Shukla et al concluded that mucocele contents often become increasingly desiccated and have higher protein content over time, leading to hyperdensity on CT scans and variable degrees of hyperintensity on T1-weighted and hypointensity on T2-weighted MRI sequences [ 2 ]. In our case, the mucocele displayed isodensity on the CT scan, low signal intensity on T1-weighted images, and high signal intensity on T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…They consist of sacs lined with epithelial cells and filled with mucus, completely occupying the sinus cavity [ 1 ]. Despite their benign nature, mucoceles can exhibit characteristics of space-occupying lesions, causing erosion of the surrounding bone and displacement of adjacent structures [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rollet (1909) предлага името мукоцеле. [1] Възможно е възникването му във всички околоносни кухини. Най-често е във фронталния синус (60% от случаите).…”
Section: въведениеunclassified